2021
DOI: 10.3390/nu13051501
|View full text |Cite
|
Sign up to set email alerts
|

Regional Difference in the Association between the Trajectory of Selenium Intake and Hypertension: A 20-Year Cohort Study

Abstract: The effect of selenium on hypertension is inconclusive. We aimed to study the relationship between selenium intake and incident hypertension. Adults (age ≥20 years) in the China Health and Nutrition Survey were followed up from 1991 to 2011 (N = 13,668). The latent class modeling method was used to identify trajectory groups of selenium intake. A total of 4039 respondents developed hypertension. The incidence of hypertension was 30.1, 30.5, 30.6, and 31.2 per 1000 person-years among participants with cumulativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…From this, we obtained the food consumption of family members and calculated the intake information of selenium as well as the total food capacity, carbohydrate, fat, and protein intake according to the Chinese Food Composition Table [29]. On the basis of the description of the same cohort, about 93% of the participants were in a stable state of selenium intake [13], so we only used the dietary intake data from 2009. The selenium intake was recoded into quartiles in the analysis.…”
Section: Exposure Variables: Selenium Intakementioning
confidence: 99%
See 1 more Smart Citation
“…From this, we obtained the food consumption of family members and calculated the intake information of selenium as well as the total food capacity, carbohydrate, fat, and protein intake according to the Chinese Food Composition Table [29]. On the basis of the description of the same cohort, about 93% of the participants were in a stable state of selenium intake [13], so we only used the dietary intake data from 2009. The selenium intake was recoded into quartiles in the analysis.…”
Section: Exposure Variables: Selenium Intakementioning
confidence: 99%
“…The middle-aged and elderly are the populations with a high incidence of various chronic diseases [11]. Studies have shown that a lack of selenium intake was associated with cognitive impairment [12], hypertension [13], and Alzheimer's disease [14,15]. In addition, considering the physiological characteristics of middle-aged and elderly people with a reduced appetite [16] and digestive capacity [17], they are at a higher risk of an insufficient selenium intake.…”
Section: Introductionmentioning
confidence: 99%
“…More recent studies have even linked Se deficiency with other comorbidities of obesity including hypertension and impaired glycemic control [ 87 , 88 ]. Importantly, Se nanoparticles were recently found to alleviate hyperlipidemia and vascular injury in ApoE - deficient mice by regulating cholesterol metabolism and reducing oxidative stress [ 89 ].…”
Section: Selenium and Thyroid Functionmentioning
confidence: 99%
“…Body mass index (BMI) was used to assess obesity levels, and the cutoff point of overweight was 24 kg/m 2 (36). Geographically, we defined Heilongjiang, Liaoning, Shandong, and Henan as the north; and Jiangsu, Hubei, Hunan, Guizhou, and Guangxi as the south (24).…”
Section: Covariatesmentioning
confidence: 99%
“…status is known for its antioxidant properties, the association between high Se intake and chronic disease remains unclear, probably attributed to its narrow safe window and other confounding factors (23,24). In previous two national studies, higher Se intake decreased the risk of hypertension in north China but increased the risk of diabetes in the United States (23,24). Furthermore, it has been pointed out that Se intake has a dose response to the incidence of diabetes and hypertension (4)(5)(6)(25)(26)(27)(28).…”
Section: Introductionmentioning
confidence: 99%